Educational requirements of management accountants in the 21st century. - Cheok, Pin Chin. (2008)
This report aims to uncover the desired work attributes of management accountants, evaluate the previous NTU accounting curriculum against employers' expectations with regards to these work attributes and assess the viability of the new curriculum.